2020
DOI: 10.1155/2020/1274591
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Activity of Yogurt Containing Raw Omija and Sugared Omija during Storage

Abstract: This study was conducted to determine the quality characteristics and antioxidant properties of yogurt containing omija extract (control, raw omija, and sugared omija) stored at 4°C for 14 days. The pH of all groups decreased, while the titratable acidity increased as the storage period increased. The viscosity of the sugared omija sample was high, while in the syneresis test, the sugared omija sample showed a low value. The total polyphenol content was the highest in the raw omija sample on day 0. DPPH activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
2
1
1
Order By: Relevance
“…This observation may suggest better stability of the pH value of yoghurt enriched with acerola than with vitamin C, presumably due to the buffering capacity of numerous other compounds present in acerola that contributed to the natural buffering capacity of yoghurt (Belwal et al, 2018 ; Salaün et al, 2005 ). The pH values of cow's yoghurts recorded in the present study were lower than the results obtained by Amal et al ( 2016 ), Cho et al ( 2020 ), and Dimitrellou et al ( 2020 ). Teichert et al ( 2015 ) showed that the pH of goat's yoghurt ranged from 4.61 to 4.63 depending on the bacterial cultures used in the experiment.…”
Section: Resultscontrasting
confidence: 83%
“…This observation may suggest better stability of the pH value of yoghurt enriched with acerola than with vitamin C, presumably due to the buffering capacity of numerous other compounds present in acerola that contributed to the natural buffering capacity of yoghurt (Belwal et al, 2018 ; Salaün et al, 2005 ). The pH values of cow's yoghurts recorded in the present study were lower than the results obtained by Amal et al ( 2016 ), Cho et al ( 2020 ), and Dimitrellou et al ( 2020 ). Teichert et al ( 2015 ) showed that the pH of goat's yoghurt ranged from 4.61 to 4.63 depending on the bacterial cultures used in the experiment.…”
Section: Resultscontrasting
confidence: 83%
“…This confirms the antioxidant activity of the Nigella sativa extract. These results are in agreement with those reported by Georgakouli et al (2016) and Cho et al (2020), where the increase in the AA of the enriched yogurts was directly related to the phenol content. The decrease in AA of yogurts during storage may be related to the milk-polyphenol interaction, which can lead to reduced antioxidant capacity.…”
Section: Evolution Of Antioxidant Activity By Dpph Inhibition Assay D...supporting
confidence: 93%
“…Similar results were observed in yogurt supplemented with germinated nigella (Nazari et al, 2023). Similar trends were observed in yogurts supplemented with sesame, with omija and with germinated black cumin seeds (Arab et al, 2020;Cho et al, 2020;Nazari et al, 2023). pH is an important factor in the processing of fermented milks, as provides information about the shelf life of yogurts.…”
Section: Sensory Analysissupporting
confidence: 77%
“…The berries are widely consumed in traditional medicine and in vitro studies on schisandra lignans have demonstrated beneficial bioactive properties such as neuroprotection, anti-cancer, antioxidant, anti-inflammatory, anti-viral, and hepatoprotective activities. 31 In food applications, the berry and its extracts are added into foods such as beer, 32 yoghurt, 33 and sausages 34 to increase antioxidant and bioactive properties, and used as a food colouring for its red pigment.…”
Section: Introductionmentioning
confidence: 99%